2016
DOI: 10.3390/catal6090134
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Hydrogenolysis of Guaiacol over Highly Dispersed Ni/MCM-41 Catalyst Combined with HZSM-5

Abstract: Abstract:A series of MCM-41 supported Ni catalysts with high metal dispersion was successfully synthesized by simple co-impregnation using proper ethylene glycol (EG). The acquired Ni-based catalysts performed the outstanding hydrogenolysis activity of guaiacol. The effects of the synthesis parameters including drying temperature, calcination temperature, and metal loading on the physical properties of NiO nanoparticles were investigated through the use of X-ray diffraction (XRD). The drying temperature was fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 45 publications
3
25
0
Order By: Relevance
“…Another B.E. peak at 855.5 eV belonged to Ni 2+ [51], with the satellite peak at the higher B.E. value.…”
Section: X-ray Photoelectron Spectroscopy (Xps)mentioning
confidence: 99%
“…Another B.E. peak at 855.5 eV belonged to Ni 2+ [51], with the satellite peak at the higher B.E. value.…”
Section: X-ray Photoelectron Spectroscopy (Xps)mentioning
confidence: 99%
“…Qiu et al reported that Ni nanoparticles supported on MCM-41 were used to catalyze the hydrogenation of guaiacol at 150 C and the conversion was 97.9%. 22 Cobalt carbonyl cluster anchored on functionalized SBA-15 showed promising catalytic activity on hydroformylation of 1-octene (97.0% conversion) with excellent selectivity towards hydroformylated product (90.0%). 23 However, these mesoporous materials could not disperse into the organic-aqueous biphase system due to their inherent hydrophilicity in the process of hydrogenation, which made the reaction conditions very harsh.…”
Section: Introductionmentioning
confidence: 99%
“…The NiO particles located inside and outside the pore of MCM-41 were used in the pyrolysis catalytic gasification of wood sawdust. The high dispersion of the fine NiO particles inside the pores of the MCM-41 support promoted the catalytic performance [18]. Haller reported that nickel was incorporated by isomorphous substitution of silicon in the MCM-41 silica framework.…”
Section: Introductionmentioning
confidence: 99%